2019
DOI: 10.3847/1538-4357/ab5803
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Magnetic Interstellar Medium in Three Dimensions over the Full Sky with Neutral Hydrogen

Abstract: Recent analyses of 21-cm neutral hydrogen (H i) emission have demonstrated that H i gas is organized into linear filamentary structures that are preferentially aligned with the local magnetic field, and that the coherence of these structures in velocity space traces line-of-sight magnetic field tangling. On this basis, we introduce a paradigm for modeling the properties of magnetized, dusty regions of the interstellar medium, using the orientation of H i structure at different velocities to map "magnetically c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
154
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(170 citation statements)
references
References 125 publications
13
154
3
Order By: Relevance
“…This approach differs from previous work where dust polarization maps are computed from a phenomenological model and ancillary observations (Planck Collaboration Int. XLII 2016; Ghosh et al 2017;Vansyngel et al 2017;Levrier et al 2018;Adak et al 2020;Clark & Hensley 2019) or directly from numerical simulations (Kim et al 2019). It follows what has been done for dust total intensity by Allys et al (2019) using the RWST, and Aylor et al (2019) using a Generative Adversarial Network.…”
Section: Random Syntheses Ofq + Iũ Polarization Mapsmentioning
confidence: 81%
“…This approach differs from previous work where dust polarization maps are computed from a phenomenological model and ancillary observations (Planck Collaboration Int. XLII 2016; Ghosh et al 2017;Vansyngel et al 2017;Levrier et al 2018;Adak et al 2020;Clark & Hensley 2019) or directly from numerical simulations (Kim et al 2019). It follows what has been done for dust total intensity by Allys et al (2019) using the RWST, and Aylor et al (2019) using a Generative Adversarial Network.…”
Section: Random Syntheses Ofq + Iũ Polarization Mapsmentioning
confidence: 81%
“…The distribution of the magnetic fields is complex but again related to the morphology of matter distribution in our galaxy. It has been shown that the integrated intensity maps processed with a rolling Hough transform [30] correlate significantly with the dust polarization angle [13,16]. However, the use of Hough transform in that work was purely phenomenological.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a natural extension of Refs. [13,16] would be to replace the integrated intensity maps with the full velocity cube and the Hough transform with a neural network in order to learn the necessary transformation. We leave this for future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we use HI emission data to identify sightlines that are potentially most susceptible to this effect. We combine information on the discrete number of HI clouds on each sightline (Panopoulou & Lenz 2020) with an estimate of the magnetic field orientation in each cloud inferred from the morphology of linear HI structures (Clark & Hensley 2019). This entirely HI-based sample selection is "agnostic" to the Planck dust polarization data.…”
Section: Introductionmentioning
confidence: 99%